Patient with polymorphic psychiatric symptoms compatible with Lujan-Fryns syndrome: case report - Fuentes-Ponce, Renzo Gonzalo (2025)
Lujan-Fryns Syndrome (LFS) is a developmental disorder of genetic origin that usually presents with neuropsychiatric symptoms such as autism, intellectual disability, aggression, and psychosis. Its heterogeneity poses a challenge for diagnosis and psychopharmacological treatment approaches. A 19-year-old male from Pucallpa, of Jewish descent, leptosomic, with no reported family history, presented marfanoid features, psychotic symptoms. He experienced psychosis, social withdrawal, obsessive thoughts, and uncontrollable impulses. After ruling out similar pathologies, he was diagnosed with LFS. He received a treatment regimen consisting of clozapine, periciazine, carbamazepine, clomipramine, and levomepromazine, achieving partial remission of psychotic and obsessive symptoms. The etiology of LFS is linked to genetic mutations, such as those affecting the MED12 gene. Diagnosis is based on the presence of clinical manifestations, such as marfanoid appearance, and the exclusion of similar conditions. Psychiatric symptoms are a characteristic feature which, in this case, were polymorphic and showed poor response to treatment. Diagnosing LFS remains a challenge in clinical settings where considering genetic entities as a cause of psychiatric disorders is uncommon. These conditions should be taken into account in the diagnostic processing of, particularly, cases of unsatisfactory therapeutic response.